Enhancing Forensic Investigations Leveraging Blockchain and Smart Contracts for Security and Transparency (International Journal of Scientific Research in Science and Technology, 2024)
The incorporation of blockchain technology into forensic investigations represents a significant advancement, tackling critical challenges within the legal and criminal justice systems. Central to this integration are smart contracts, which automate and secure essential aspects of investigations. These self-executing agreements operate based on predefined rules, ensuring integrity and transparency in tasks such as evidence tracking, chain of custody management, and access control. A key advantage lies in the substantial enhancement of data security. Blockchain’s cryptographic principles and decentralized structure make it highly resistant to unauthorized access and tampering, crucial in maintaining evidence integrity. Additionally, blockchain’s immutability ensures the reliability of information; once recorded, data becomes virtually unalterable, providing an indisputable ledger of events. In summary, this innovative integration streamlines operations, reduces errors and disputes, and strengthens the trustworthiness of forensic investigations by offering an unforgeable and transparent chain of custody and evidence history within the legal and criminal justice framework.